Incidence and susceptibility pattern of clinical isolates from pus producing infection to antibiotics and Carica papaya seed extract (2011)
"The prevalence of bacterial pathogens isolated from pus producing infections (wound, eye and ear) randomly collected from the Medical Microbiology Laboratory of University College Hospital (UCH), Ibadan, Nigeria was determined. Their susceptibility to selected antibiotics and Carica papaya seed extracts was investigated. Bacterial pathogen identity was confirmed based on standard methods which included, Gram stain reaction, colonial morphology on media, lactose fermentation, catalase,oxidase,coagulase and indole tests. The antibiogram was carried out using standard disc agar diffusion method employing commercially prepared antibiotic disc (Abtek Limited) of amoxycillin (25mcg), co-trimoxazole (25 mcg), nitrofurantoin (300 mcg), gentamicin (10 mcg), nalidixic acid (30 mcg),ofloxacin (30 mcg), augmentin (30 mcg) and tetracycline (10 mcg). A total of 58 isolates were obtained out of which 31 were from wound, 12 from ear and 15 from eye. 41 of the isolates were recovered from adults, while 17 were from children. Staphylococcus aureus was found to be the most common organism recovered (51.7%), followed by Klebsiella spp. (11%), Pseudomonas aeruginosa (11%),Proteus spp. (6.9%) and Escherichia coli (3.4%). From wound swabs, S. aureus isolates was the highest (51.6%) followed by Klebsiella spp. (22.6%), Pseudomonas aeruginosa and Proteus spp. (9.7% each) and E. coli (6.45%). In ear infection, P. aeruginosa accounted for 58.3%, S. aureus 25%, while Klebsiella spp. and Proteus spp. accounted for 16.6% each. In eye infection, S. aureus and Klebsiella spp. were more frequently isolated with 73.3 and 20%, respectively. The antibiogram studies showed that all the organisms were highly sensitive to ofloxacin as follows: S. aureus (80%), Klebsiella spp. (100%), P. aeruginosa (100%), Proteus spp. (100%) and E. coli (100%) while P. aeruginosa (63.6%), S. aureus (76.6%) and E. coli (100%) were sensitive to gentamicin and Klebsiella spp. (18.2%) and Proteus spp. (25%) were resistant. The organisms were resistant to all the other antibiotics tested namely: amoxycillin, co-trimoxazole, nitrofurantoin, nalidixic, augmentin and tetracycline. C. papaya extract showed antimicrobial activity which compared favourably with the commercial antibiotic discs against the Gram positive and negative bacteria tested, except Klebsiella spp. The highest activity was demonstrated against P. aeruginosa."